ผลของการฟอกสีฟันต่อความทนแรงดึงของเคลือบฟันและเนื้อฟัน - จรรยา สุระกำพลธร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
Objective: To evaluate the tensile strength of enamel and dentin after extracoronal bleaching with in-office and home bleaching techniques or intracoronal bleaching. Methods: Extracted bovine incisors were divided into 8 groups of ten specimens. Extracoronal bleaching using different concentrations of hydrogen peroxide (H) and carbamide peroxide (C) were treated in each group : 1. 35%H and 10%C (E35H-10C) 2. 35% H and 20%C (E35H-20C) 3. 35%C and 10%C (E35-10C) 4. 35%C and 20%C (E35C-20C) and no bleaching in control group (EC). Intracoronal bleaching was performed after 24 hours of root canal treatment using either combination of sodium perborate and 35%H (ISP-35H) or sodium perborate and distilled water (ISP-W) or no bleaching in control group(IC). Bleaching techniques were operated as manufactures recommendations. Minidumbells of enamel and dentin with the cross-sectional central area of 1.5x0.5 mm2 and 3x1 mm2 respectively were prepared for tensile testing with lnstron machine. Fracture surfaces were examined using SEM. Results Tensile strengths (Means±SD) in MPa of enamel of each group were : EC = 30.51 ± 3.34 E35H-10C = 14.82 ± 2.33 E35H-20C = 10.64 ± 2.54 E35C-10C = 25.37 ± 3.40 E35C-20C = 20.30 ± 4.06 IC = 26.48 ± 4.08 ISP-35H = 13.60 ± 3.06 ISP-W = 21.10 ±6.39. With ANOVA and Tukey HSD test. It was found that the tensile strengths from all extracoronal bleaching groups were significantly different from one another and also from the control(p < 0.05). Similar results were obtained among intracoronal bleachng groups and the control(p < 0.05). Tensile strengths (Means±SD) in MPa of dentin of each group were : EC = 85.35 ± 3.03 E35H-10C = 58.87 ± 1.95 E35H-20C = 55.46 ± 2.20 E35C-10C = 70.79 ± 2.52 E35C-20C = 67.20 ± 3.26 IC = 85.88 ± 2.46 ISP-35H = 46.73 ± 2.77 ISP-W = 68.30 ± 4.42. With ANOVA and Tukey HSD test, it was found that the tensile strengths from all extracoronal bleaching groups were significantly different from one another and also from the control(p < 0.05). Similar results were obtained among intracoronal bleaching groups and the control(p < 0.05). Fracture surfaces showed that the higher the concentration of hydrogen peroxide. The higher the microporosity in both enamel and dentin. Conclusion : Extracoronal and intracoronal bleaching decreased the tensile strengths of both enamel and dentin.